The Views of Educators and Thinkers Who Influenced Education Policies in the Ottoman Period - Ethem Gürhan,; Sabahattin Çiftçi, (Journal of Educational Issues, 2024)
Intellectuals and thinkers, who are influential on the society, have an influence on the people they live with their ideas, especially on the growing generations. It is seen that this intelligentsia, who leads and guides the society they live in, deeply affects the life of society. The works of these people, who have important roles in shaping the society in which they live with their thoughts, are adopted by the individuals in that society and their influence on the generation that has grown for many years is seen to last. The works of these people adopted by the society and their thoughts in these works are shown as examples in the educational institutions of that society and read as textbooks. For this reason, the opinions of educators and thinkers in that society have an impact on the growing generation. Surely, when we look at the Ottoman period, the number of educators and thinkers who had an impact on society is quite high. However, it is not possible to address all of them. That is not the point of this research. The important criterion in this research is the most important educators and thinkers of each period. In particular, they are educators and thinkers who have basic works on education and whose works have been taught in schools as textbooks for many years, and who have significant effects on social life. When we look at these thinkers, we can see that their influence continues from past to present. In this research, the document review pattern, which is one of the qualitative research methods, was used and it was determined that the findings of the research were dominated by the view that educational policies based on moral values and aiming to be trained in line with the abilities of the student should be applied in the ottoman period human education policies. In addition, it is seen that the first step of physically transitioning from madrasa system to today’s modern school and classroom system was taken by Selim Sabit Efendi.